Optimization of Robot Telemonitoring System Software using multi-thread method - Midriem Mirdanies (INKOM Journal, 2017)
The processor development today is on multi-core and multi-processor which can be used to a speedup of data processing time compared with one processor core only. One of the main ways that can be used to speed up the data processing time is by using multi-thread. Multi-thread method has been implemented on the robot telemonitoring system based a Graphical User Interface (GUI) which has been developed in Research Center for Electrical Power and Mechatronics, Indonesian Institute of Sciences (LIPI). A part that requires high processing time at the telemonitoring systems are the display of real-time thermal cameras and color camera along with tracking algorithm used, it can be seen from the thermal camera display which less smooth. Two threads have been added to process each of the cameras separately. C programming language, with the opencv library and the Integrated Development Environment (IDE) Qt Creator has been used to implement this method into an application program. Based on experiments, it can be seen that both of the camera display with tracking algorithm used can run more quickly, it is demonstrated with the smooth display and the processing time is faster than a sequential program. The processing time based cpu time in sequential program both on color camera and thermal camera is 6 fps, while in multi-thread program (with added two threads), the processing time is 6 fps for color cameras and thermal camera is become 7 fps. The processing time based wall clock time in the sequential program on color camera and thermal camera is 6.31579 fps, while in multi-thread program (with added two threads), the processing time is 6.31579 fps for color cameras and thermal camera becomes 7.5 fps. The speedup and efficiency obtained between the sequential program and with added two threads are 0.84211 and 0.28070. Keywords: multi-thread, telemonitoring, GUI, Qt creator, c language